The treasure trove of the genus Carex: A phytochemical and pharmacological review - Rahul Gajbhiye; Shreya Sen Sarma; Deepak Kumar; Sanjiv Singh (Health Sciences Review, 2024)
Carex genus contains over 2000 species distributed all around the globe and used for their medicinal and food values. Owing to their traditional and medicinal properties the genus has gained due attention, especially in the last couple of decades which led to the identification of terpenoids, lignans, quinazolinones, phenolic acids, and phenylpropanoids as the major phytochemicals. Besides these several studies reported the therapeutic applications of the extracts and phytochemicals in different experimental conditions. The present review aims to present a comprehensive overview of the present standing of Carex genus that may promote further scientific exploration and their utilization.